The really useful elearning instruction manual : your toolkit for putting elearning into practice - Hubbard, Rob, 1975- (Wiley, 2013)
From the world's leading experts in the field, everything you need to know to start an e-learning program in your organization The range of e-learning technologies and options has expanded significantly over the past several years. Unfortunately, not all of them are good. Written by a team of experts from the eLearning Network, this book arms you with the knowledge you need to sort through the vast array of e-learning options now available and the skill to start putting the best to work in your organization immediately. Edited by Rob Hubbard and featuring chapters written by leading global e-learning professionals: Clive Shepherd, Laura Overton, Jane Bozarth, Lars Hyland, Rob Hubbard, Julie Wedgwood, Jane Hart, Colin Steed, Clark Quinn, Ben Betts and Charles Jennings 'along with additional comments and commentary from twenty eLearning Network members'this manual covers all the bases for HR managers, team leaders, trainers, learning development professionals and all those excited by the many exciting opportunities provided by today's more sophisticated and dynamic world of digital education.-Practical coverage of all key topics in e-learning'including marketing and communications, development, blended learning, mobile learning, game-based learning and more -Written by the experts at eLearning Network, a global not-for-profit association of e-learning professionals dedicated to sharing knowledge and best practices in all e-learning areas -Online access to a wealth of additional materials, including podcasts, videos, blogs, twitter streams and more -Generously illustrated and packed with real-life examples, case studies, stories and tips from more than thirty e-learning experts.